SISTEM PENGOLAHAN DATA INVENTARIS PERALATAN PRAKTEK PADA SMK PRASASTI KARANG BERAHI KOTA JAMBI: APPLICATIONS, FRAMEWORK, INFORMATION, INVENTORY, MYSQL, PHP. - Limia Budiarti, Rike; Wahid, Nur (LP2M STMIK Nurdin Hamzah Jambi, 2017)
SMK Prasasti Karang Berahi Jambi city in the inventory data processing system is still done manually by taking notes on the diary and most of the data input using Microsoft Office applications. The problems can inconvenient admin officers who manage inventory data because it must run several different application programs to process inventory data. In order to process data inventory efficiently, we need to build an application program that can use simultaneously and can run on all computers. The purpose of this study is to build equipment practice data inventory processing to offer ease performing of the data inventory management process. The application built using web-based technology with PHP scripting language, MySQL database, and Framework. The result of Web-based Inventory Data Processing System implementation expected to help staff in delivering a hardware inventory data collection administrative data online and real-time.